Elements of port operation and management - Branch, Alan E (Chapman and Hall, 1986)
This book has been written to provide a practical, overall understanding of the elements of port operation and management of a competitive, profitable port authority. It deals in simple language with the role and function of seaports in a trading pattern, port investment criteria, port tariffs, free ports and free trade zones, port traffic control, budgetary control and marketing, port mananagemet structure and dock labour, computerization, carga-handling equipment, the economics of ports design, the role of port cargo-handling organization, the economics of international trade, finance of international trade and many other aspects of this extensive subject.